2007
DOI: 10.1590/s0004-282x2007000500001
|View full text |Cite
|
Sign up to set email alerts
|

Intensive insulin therapy versus conventional glycemic control in patients with acute neurological injury: a prospective controlled trial

Abstract: -Objective: To compare intensive insulin therapy to conventional glycemic control in patients with acute neurological injury evaluating neurological outcome and morbimortality. Method: Patients with two glycemias above 150 mg/dL 12 hours after admission were randomized to receive intensive insulin therapy (G1) or conventional treatment (G2). We evaluated a subgroup of patients with acute brain injury from July, 2004 to June, 2006. Results: G1 patients (n=31) received 70.5 (45.1-87.5) units of insulin/ day whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 17 publications
0
21
1
Order By: Relevance
“…Bilotta et al (2008) and Coester, Neumann, and Schmidt (2010) limited participants to patients with GCS scores of less than 8 and/or utilized CT to diagnose a mass or a lesion. de Azevedo et al (2007) showed to have a mean GCS that was slightly higher than in the other studies, with the experimental group being 9.5 and the control group being 10.2, suggesting a less severe baseline condition.…”
Section: Literature Review Injury Severitycontrasting
confidence: 57%
See 2 more Smart Citations
“…Bilotta et al (2008) and Coester, Neumann, and Schmidt (2010) limited participants to patients with GCS scores of less than 8 and/or utilized CT to diagnose a mass or a lesion. de Azevedo et al (2007) showed to have a mean GCS that was slightly higher than in the other studies, with the experimental group being 9.5 and the control group being 10.2, suggesting a less severe baseline condition.…”
Section: Literature Review Injury Severitycontrasting
confidence: 57%
“…Four of the studies in this review (de Azevedo et al, 2007;Graffagnino et al, 2010;Green et al, 2010;Wittenberg et al, 2008) looked at patients with diagnoses who were admitted to a neurocritical care ICU ( Subpopulations not expanded on.…”
Section: Literature Review Injury Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical neuroprotective effects included reduction of intracranial pressure, reduction of seizures, and better long-term rehabilitation in patients with isolated brain injury, together with a lower incidence of critical illness-induced neuromyopathy. Subsequent randomized controlled studies in critically ill patients with acute brain injury [57][58][59][60][61][62][63] or with acute ischemic stroke [64][65][66] showed mostly no benefit in terms of neurological outcomes (Table 2). A recent systematic review on acute ischemic stroke concluded that intravenous insulin administration aiming to maintain serum glucose within a specific range did not improve the neurological deficit [67].…”
Section: Is Blood Glucose Control With Insulin During Critical Illnesmentioning
confidence: 99%
“…Since the publication of the first Leuven study in 2001, 1 which showed that normalization of hyperglycemia by intensive insulin treatment with a targeted blood glucose of 4.4-6.6 mmol/L compared with conventional glycemic control (glucose target, 10-11.1 mmol/L) resulted in an absolute reduction in mortality (4.6% vs. 8%, P < 0.04) in a surgical intensive care unit (ICU), subsequent trials have added confusion, rather than confirmed these initial findings. The many clinical trials and interventions set up to confirm the benefit of normalizing hyperglycemia in different clinically ill populations failed to do so [2][3][4][5] and suggested that results may differ between admission diagnosis, [6][7][8][9] between type of ICU, 2,4,5,10,11 or between patients with or without previously diagnosed diabetes. [1][2][3][4]10,12,13 The largest and perhaps most important trial was the multicenter randomized controlled NICE-SUGAR study in 2009.…”
mentioning
confidence: 99%